PERLINDUNGAN HUKUM BORROWER ATAS PENGGUNAAN DATA PRIBADI TANPA IZIN OLEH LAYANAN PINJAMAN ONLINE - William Martin Aruan; I Ketut Suardita (KOLONI, 2023)
This research aims to comprehend the legal protection provided to borrowers regarding the unauthorized use of personal data by online lending services, as well as identify the legal remedies available to borrowers in such scenarios. The normative legal research method with a statutory and factual approach has been employed in this paper. The findings indicate that borrowers are entitled to both preventive and repressive legal protection in the financial services sector. To resolve disputes, borrowers have the option to seek legal recourse through litigation/court or opt for alternative dispute resolution mechanisms offered by institutions operating in the financial services sector.  Keywords: borrowers, online loans, personal data, without permission